2018
DOI: 10.1038/s41598-018-31870-z
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput sequencing revealed that microRNAs were involved in the development of superior and inferior grains in bread wheat

Abstract: High-throughput sequencing was employed to investigate the expression of miRNAs and their target genes in superior and inferior seeds of Aikang 58. Small RNA sequencing revealed 620 conserved and 64 novel miRNAs in superior grains, and 623 conserved and 66 novel miRNAs in inferior grains. Among these, 97 known miRNAs, and eight novel miRNAs showed differential expression between the superior and inferior seeds. Degradome sequencing revealed at least 140 candidate target genes associated with 35 miRNA families … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…In wheat, about a dozen studies have been performed on miRNA identification using sRNA sequencing (sRNA-Seq) (Yao et al, 2007; Wei et al, 2009; Li et al, 2013; Meng et al, 2013; De Paola et al, 2016; Fileccia et al, 2017; Wang et al, 2018). miRNAs responding to diverse stresses in wheat have also been reported (Xin et al, 2010; Zhou et al, 2015; Akdogan et al, 2016; Chen et al, 2017; Zuluaga et al, 2017; Han et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In wheat, about a dozen studies have been performed on miRNA identification using sRNA sequencing (sRNA-Seq) (Yao et al, 2007; Wei et al, 2009; Li et al, 2013; Meng et al, 2013; De Paola et al, 2016; Fileccia et al, 2017; Wang et al, 2018). miRNAs responding to diverse stresses in wheat have also been reported (Xin et al, 2010; Zhou et al, 2015; Akdogan et al, 2016; Chen et al, 2017; Zuluaga et al, 2017; Han et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs responding to diverse stresses in wheat have also been reported (Xin et al, 2010; Zhou et al, 2015; Akdogan et al, 2016; Chen et al, 2017; Zuluaga et al, 2017; Han et al, 2018). miRNAs related to the development and filling of wheat seeds have been studied (Meng et al, 2013; Han et al, 2014; Li et al, 2015; Wang et al, 2018). For example, Meng et al (2013) identified 104 miRNAs associated with grain filling in wheat.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, a short-tandem target mimic (STTM) method was used to verify if miR166 regulates important agronomic traits in rice . In a study, transgenic STTM165/166 plants showed significantly reduced seed number and sterile siliques in Arabidopsis, suggesting that miR166 plays a vital role in seed development and it might be useful evidence to improve inferior grain size in wheat (Wang et al, 2018). Among the detected and annotated genes in the MQTLs regions in this study, the OsMED9 (TraesCS3B02G077100), which is an orthologous gene of rice, was identified in the MQTL_3B_1 region that was associated with GY and its components.…”
Section: Mqtls and Functional Candidate Genesmentioning
confidence: 63%
“…Additionally, novel miRNAs were predicted from unannotated sequences without similarity to known miRNAs (Additional file 2: Table S2, Additional file 3: Table S3). Since many miRNAs have not been deposited into miRBase, the novel miRNAs identified in this study were also compared with previously published wheat miR-NAs [12,[14][15][16][31][32][33][34][35]. In total, the sequences of 39 miRNAs from among the newly identified miRNAs were the same as those of previously found novel miRNAs (Table S2; the miRNAs are labeled in yellow).…”
Section: Identification Of Known Mirnas and Predicted Novel Mirnasmentioning
confidence: 99%
“…In rice, osa-miR167 regulates the auxin-miR167-ARF8-OsGH3.2 pathway, which functions during grain filling [13]. High-throughput sequencing revealed that the differentially expressed miRNAs between superior and inferior wheat grain are likely related to cell division, carbohydrate metabolism and hormone biosynthesis [14]. Han et al [15] demonstrated that miR164, miR160, and miR169 show different expression profiles during grain filling, suggesting that their functions are coordinated during the different stages of wheat seed development.…”
Section: Introductionmentioning
confidence: 99%